2009
DOI: 10.1038/jp.2009.120
|View full text |Cite
|
Sign up to set email alerts
|

Serum thrombopoietin level and thrombocytopenia during the neonatal period in infants with Down's syndrome

Abstract: Background: The pathogenesis of thrombocytopenia during the neonatal period in Down's syndrome (DS) infants remains unclear.Objective: To elucidate kinetic changes of serum thrombopoietin (TPO) level and platelet count, and their correlation in DS neonates.Study Design: Twelve DS infants (male/female: 7/5, term/late preterm: 10/2) born between 1997 and 2007 were included. Blood samples were serially collected during the neonatal period and serum TPO levels were determined in 44 sera using an enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
3
5
0
1
Order By: Relevance
“…1,16 Hord et al 23 noted that the most likely explanation for thrombocytopenia in infants with trisomy 21 is the presence of megakaryocytic dysregulation, a phenomenon previously described in the development of transient myeloproliferative disorder and acute nonlymphoblastic leukemia in these infants [24][25][26][27] ; this dysregulation may involve thrombopoietin levels. 28 Of note, using a definition of < 100,000/mm 3 , our overall incidence of thrombocytopenia was similar to that observed by Hord et al 23 in a smaller study (35% versus 28%, respectively; p ¼ 0.51). Dixon et al 20 reported that thrombocytopenia was more likely in neonates who had polycythemia.…”
Section: Discussionsupporting
confidence: 89%
“…1,16 Hord et al 23 noted that the most likely explanation for thrombocytopenia in infants with trisomy 21 is the presence of megakaryocytic dysregulation, a phenomenon previously described in the development of transient myeloproliferative disorder and acute nonlymphoblastic leukemia in these infants [24][25][26][27] ; this dysregulation may involve thrombopoietin levels. 28 Of note, using a definition of < 100,000/mm 3 , our overall incidence of thrombocytopenia was similar to that observed by Hord et al 23 in a smaller study (35% versus 28%, respectively; p ¼ 0.51). Dixon et al 20 reported that thrombocytopenia was more likely in neonates who had polycythemia.…”
Section: Discussionsupporting
confidence: 89%
“…In a study of patients with thyroid dysfunction, Yu HM et al showed that SCH and RDW were associated significantly when patients with SCH and the control group were compared [17]. RDW and serum TSH levels were reported to be associated significantly in another study [18]. In our study, we found that RDW was significantly higher in patients with DS compared to the control group.…”
Section: Discussionsupporting
confidence: 60%
“…When TPO was included in the model, it was found to play a significant role in both the MCI‐DS and DS‐AD proteomic profiles spanning fractions. TPO is a known glycoprotein hormone that aids in the production of platelets 24,25 and in DS, TPO has been almost exclusively studied among pediatric cases due to high level of thrombocytopenia 26‐28 . Although TPO exhibited an unexpectedly high CV for plasma (and was initially excluded from derived protoemic profiles), the inclusion of TPO did not significantly change the detection accuracy of the proteomic profiles despite its prominence within the models.…”
Section: Discussionmentioning
confidence: 99%